Estimation of food and nutritional security in azerbaijan: a case study of the Ganja-Gazakh region - Huseynov, Ragif (Studia Mundi – Economica, 2020)
This paper seeks to estimate household food security situation in the Ganja-Gazakh region of Azerbaijan based on both rural and urban areas of the Ganja-Gazakh region by identifying the food consumption and nutritional security situation of individual households. Primary data was generated from 300 households through simple random sampling. A face to face survey interview was conducted to collect quantitative and qualitative data on food and nutritional security such as availability, access, utilization, and stability. The Dietary intake method (DIA) was applied to estimate the food and nutritional security of households with the help of 7 days’ recall method. The empirical results showed that besides the adequate food availability situation, the problem of malnourishment is still existing among both urban and rural households of Ganja-Gazakh region of Azerbaijan. More than 20 percent of households were found food insecure in the selected region. Likewise, the situation of nutritional security was also estimated. It the study revealed that most of the households were undernourished. The present level of protein, zinc, and iron was low among households. The condition of micro and macronutrients was severe. Based on the findings of this study, there is urgent need for the government to launch short and long term public and private programs to overcome the issue of food and nutritional insecurity rural and urban areas of Azerbaijan.